Proximity to AGCT sequences dictates MMR-independent versus MMR-dependent mechanisms for AID-induced mutation via UNG2. Issue 6 (30th December 2016) - Thientosapol, Eddy Sanchai; Sharbeen, George; Lau, K.K. Edwin; Bosnjak, Daniel; Durack, Timothy; Stevanovski, Igor; Weninger, Wolfgang; Jolly, Christopher J.
Abstract: AID deaminates C to U in either strand of Ig genes, exclusively producing C:G/G:C to T:A/A:T transition mutations if U is left unrepaired. Error-prone processing by UNG2 or mismatch repair diversifies mutation, predominantly at C:G or A:T base pairs, respectively. Here, we show that transversions at C:G base pairs occur by two distinct processing pathways that are dictated by sequence context. Within and near AGCT mutation hotspots, transversion mutation at C:G was driven by UNG2 without requirement for mismatch repair. Deaminations in AGCT were refractive both to processing by UNG2 and to high-fidelity base excision repair (BER) downstream of UNG2, regardless of mismatch repair activity. We propose that AGCT sequences resist faithful BER because they bind BER-inhibitory protein(s) and/or because hemi-deaminated AGCT motifs innately form a BER-resistant DNA structure. Distal to AGCT sequences, transversions at G were largely co-dependent on UNG2 and mismatch repair. We propose that AGCT-distal transversions are produced when apyrimidinic sites are exposed in mismatch excision patches, because completion of mismatch repair would require bypass of these sites.